Observation of current-induced switching in non-collinear antiferromagnetic IrMn3 by differential voltage measurements - Sevdenur Arpaci (Nature Portfolio, 2021)
Anti-ferromagnetic based memories have a wide range of advantages over their ferromagnetic counterparts, however, their electrical signatures of switching are complicated by spurious signals. Here, Arpaci et al demonstrate an experimental method to distinguish between anti-ferromagnetic switching, and such spurious signatures.